1988
DOI: 10.3758/bf03209048
|View full text |Cite
|
Sign up to set email alerts
|

Human-based social interaction can reward a rat’s behavior

Abstract: Rats were trained to leverpress in a conventional operant test chamber; however, their behavior was rewarded solely by social interaction with a human being. This training was successful for half the subjects tested; success was confined to animals for which social interaction had occurred prior to training. Similar findings with other species are discussed. Although the effects of social interaction with a human are by no means as robust as those of food to a hungry animal, the present results suggest that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…This is not to say that rats, or other laboratory/prey species, are not capable of forming meaningful bonds with humans. Indeed, we have previously demonstrated that laboratory rats will work in a Skinner box for petting by a preferred human in the absence of traditional reward such as food or water (Davis and Perusse 1988). It is unlikely, however, that romantic notions like friendship have much to do with the behavior demonstrated in our experiments.…”
Section: Preference Testingmentioning
confidence: 84%
“…This is not to say that rats, or other laboratory/prey species, are not capable of forming meaningful bonds with humans. Indeed, we have previously demonstrated that laboratory rats will work in a Skinner box for petting by a preferred human in the absence of traditional reward such as food or water (Davis and Perusse 1988). It is unlikely, however, that romantic notions like friendship have much to do with the behavior demonstrated in our experiments.…”
Section: Preference Testingmentioning
confidence: 84%
“…It is not clear, however, whether human-based socialization is essentially positive, as the findings of Davis and Perusse (1988) suggest, or whether such contact serves to habituate neophobia. Although it is difficult to label the present experience in terms of conventional laboratory procedures, we believe the human contact offered in Experiments I, 3, and 4 allows for the formation of an association between a particular human CS and positive hedonic events.…”
Section: Discussionmentioning
confidence: 99%
“…Handling can lead to a fearful relationship with humans (Davis and Pérusse, 1988;Hurst and West, 2010), making handling difficult, increasing the risk of injury for both handler and animal, and limiting both the internal and external validity of research data (Sherwin, 2004).…”
Section: Introductionmentioning
confidence: 99%